2017
DOI: 10.7752/jpes.2017.02080
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:Investigated here were correlations between factors characteristic of competitive sports, for instance, type of athletic event and level of competition and the dark triad-Machiavellianism, psychopathy, and narcissism. A questionnaire survey was conducted with 506 Japanese university athletes (217 male and 289 female, mean age = 19.9, SD = 0.8). Three-way analysis of variance (ANOVA) indicated significant and marginally significant main effects of gender (male/female), type of athletic event (record-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…In contrast, athletes with welladjusted levels of narcissism strive to achieve their goals and act on their talents and abilities [15][16][17][18]. In this regard, Unoe et al [21] examined the correlation between competitive sports and dark personality traits; they concluded that the effects of gender, type of sports activity, and level of competition in which athletes are involved largely affect the total score of dark personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, athletes with welladjusted levels of narcissism strive to achieve their goals and act on their talents and abilities [15][16][17][18]. In this regard, Unoe et al [21] examined the correlation between competitive sports and dark personality traits; they concluded that the effects of gender, type of sports activity, and level of competition in which athletes are involved largely affect the total score of dark personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mental toughness has negative indirect effects on the relationships between the triple factors of dark personality. In other words, narcissism increases the level of mental toughness and mental toughness decreases the level of Machiavellianism and psychopathy [15]. According to the above findings and the findings of Sabouri et al (2016), it is clear that there is a deep relationship between physical activity, the triple factors of dark personality, and mental toughness.…”
Section: Introductionmentioning
confidence: 57%
“…Also, it will reduce the negative image of sports as a result of unfair competition [18]. Ueno et al (2017) [15] concluded that the correlation between the triple factors of dark personality and athletes' gender, the type of sports event, and the level of competition, clearly indicate the importance of future research regarding this dimension of athletes' personality and the process of their sports performance and behavioral problems [15]. Although in some studies, the effect of Machiavellianism on the happiness of athletes and non-athletes was insignificant, it was positive and significant in non-violent sports, and the psychopathy factor had an inverse and significant effect on the happiness of athletes and non-athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaughan et al hypothesized that the Dark Triad traits measured by SD3 would vary across different performance levels [13]. Other studies also focused on similar research topics and tested for similar results through empirical research [4,[14][15]. As for the overall Dark Triad score, gender differences, level differences, and sport-type differences were presented across these studies.…”
Section: Dark Triadmentioning
confidence: 99%